Developing a risk-informed decision-support system for earthquake early warning at a critical seaport. (February 2022) - Cremen, Gemma; Bozzoni, Francesca; Pistorio, Silvia; Galasso, Carmine
Abstract: Earthquake early warning (EEW) systems are used to provide timely alerts on ongoing earthquakes, which can facilitate important risk-mitigation actions before potentially damaging seismic waves reach target sites. A major shortcoming of existing EEW approaches is that the earthquake-related conditions for activating alerts are not generally defined according to a formal decision-support system (DSS) that accounts for possible risk-based consequences of triggering/not triggering the alarm. This paper exploits a next-generation risk-informed EEW DSS, which incorporates multi-criteria decision-making for evaluating the optimal decision. The proposed DSS integrates engineering-driven loss predictions associated with issuing/not issuing an EEW alert during an event, also considering possible system malfunctions. The DSS is demonstrated for the strategic Gioia Tauro seaport, located in a region with some of the highest seismic hazard in Italy. Real-time seismic risk analyses are conducted for various earthquake scenarios, accounting for event-parameter uncertainties that are integral to any EEW process and considering the multicomponent nature of the port as a system of interconnected elements. The results of these analyses are used as input to the proposed EEW DSS along with end-user risk preferences, to evaluate the optimal decision in each case and to define a series of risk-informed EEW warning thresholds for the port. Highlights: The system integrates seismic risk predictions and multi-criteria decision-making. The system identifies the optimal action (issue or not a warning) for a given event. The optimal action can be sensitive to stakeholder risk preferences. The optimal action can depend on the level of functionality interdependence captured.